Maternity Nurses' Knowledge and Practice of Breastfeeding in Mississippi. Issue 4 (July 2018) - Alakaam, Amir; Lemacks, Jennifer; Yadrick, Kathleen; Connell, Carol; Choi, Hwanseok Winston; Newman, Ray G.
ABSTRACT: Background: Mississippi has the lowest rates of breastfeeding of all states at 6 months and at 1 year. Registered nurses working in the maternity setting can be influential in mothers' decision to breastfeed. Purpose: The purpose of this study was to examine registered nurses' knowledge and practice related to breastfeeding; and to identify facilitators and barriers to implementing the Ten Steps to Successful Breastfeeding in Mississippi hospitals. Methods: 302 Registered nurses working in hospital maternity/birthing settings in Mississippi completed a questionnaire. Breastfeeding knowledge and practices overall scores were categorized into: poor and good. Chi-square analysis and Spearman correlations were used to determine correlations among the variables. Results: Overall breastfeeding knowledge and practices of respondents was good. Only 4% earned a perfect score. Most believed they were effective (77%) in meeting the needs of new mothers. Significant positive associations were noted among knowledge and effectiveness, and other variables. Resistance to change and staffing shortages were the main barriers to implementing the Ten Steps; raising awareness about the importance of the Ten Steps and providing a lactation consultant were the main facilitators. Conclusion: More research is needed to understand reasons behind low breastfeeding rates in Mississippi. Abstract : Mississippi has the lowest rate of breastfeeding initiation and for babies at 6 months of age of any state in America. This study evaluated maternity nurses' knowledge of breastfeeding and their perceptions of barriers to implementing the Ten Steps to Successful Breastfeeding in their clinical practice. Overall knowledge was good but barriers to the Ten Steps included short-staffing, inadequate education about breastfeeding, and resistance to change.